Social comparison in parents of children with chronic conditions: results from the Portuguese version of the Iowa-Netherlands Comparison Orientation Measure - Mendes, Teresa (2019)
ABSTRACT: Aim: The Iowa-Netherlands Comparison Orientation Measure (INCOM) is a measure for assessing individual differences in social comparison orientation. Despite the relevance of social comparison orientation in understanding adult patients' adjustment responses to chronic health conditions, the impact of parental social comparison processes in the context of chronic pediatric conditions remains unexplored. This study’s main goal was to examine the psychometric properties of the Portuguese version of the INCOM with parents of children with chronic health conditions. Method: Two samples of parents of children with chronic pediatric conditions (asthma, epilepsy, diabetes and obesity) were used (test sample, N = 301; validation sample, N = 192). Parents completed self-reported measures of social comparison orientation, anxiety and depression symptoms and neuroticism. Results: Regarding factorial validity, results supported the unidimensionality of a revised INCOM scale, comprised of nine items. Results also supported the reliability of the measure, and provided evidence of concurrent validity: parents with higher social comparison orientation presented more anxiety and depressive symptoms, and higher neuroticism scores, consistent with what was theoretically expected. Conclusion: This study opens an important door in the field of pediatric chronic conditions, supporting the relevance of examining parents’ social comparison differences in future research, and the utility of the INCOM in the assessment of those differences.